Biosynthesized silver nanoparticles anchored on a carbon material derived from maple leaves for the development of a green non-enzymatic biosensor for creatinine sensing - Barreto, Francisco Contini [UNESP]; Barberis, Maria Eduarda [UNESP]; Mounienguet, Naelle Kita [UNESP]; Ito, Erika Yukie [UNESP]; da Silva, Martin Kássio Leme [UNESP]; He, Quan; Cesarino, Ivana [UNESP] (Elsevier, 2025)
Creatinine (CRE) is a byproduct of creatine and phosphocreatine breakdown in muscles, produced at a relatively constant rate and excreted by the kidneys, making it a critical biomarker for assessing renal function. This study reports the development of a novel, eco-friendly non-enzymatic biosensor for CRE determination in synthetic urine. A carbon material was derived from maple leaves and used to anchor biosynthesized silver nanoparticles (HC-AgNPs) prepared from fresh grass. This composite was employed to modify a glassy carbon electrode (GC/HC-AgNPs) for CRE detection. Due to CRE's strong affinity for specific metals, the reduction in silver oxidation peaks served as an indicator of CRE presence in solution. The synthesized composites were characterized by scanning electron microscopy, energy-dispersive spectroscopy, cyclic voltammetry, and spectrophotometry. The sensor exhibited a linear response range of 100–500 µmol L⁻¹, with detection and quantification limits of 26.1 and 86.1 µmol L⁻¹, respectively, using square wave voltammetry. Recovery rates in synthetic urine were of 105.60% and 106.89%, with selectivity experiments revealing recovery percentages exceeding 92% for tested molecules. This sustainable and cost-effective biosensor aligns with green chemistry principles, offering a promising alternative for CRE detection.
Keywords: Creatinine; Electrochemical sensor; Green chemistry; Hydrochar; Maple leaves